2016
DOI: 10.1111/basr.12081
|View full text |Cite
|
Sign up to set email alerts
|

A Swiss‐Army Knife? A Critical Assessment of the Extractive Industries Transparency Initiative (EITI) in Ghana

Abstract: Within the current global atmosphere where a universally accepted police force is nonexistent, there are several voluntary norms and codes of conduct that exist to guide how corporations behave worldwide. These have come as a result of many years of poor performance in the areas of social, financial, and environmental responsibility. Such norms are expected to prescribe and proscribe certain types of corporate behavior but when one examines the reality on the ground, the story is not that straightforward. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Unfortunately, available evidence on corporate disclosure indicates otherwise – as Brown et al (2009: 572) found in their analysis of the Global Reporting Initiative Sustainability Reporting Guidelines, corporate information disclosure had ‘little impact in shifting the balance of power in corporate governance toward civil society’. Since its launch in 2002, there have been extensive studies about the effectiveness of EITI particularly in the conflict regions of Africa (Andrews, 2016; Haufler, 2010; Hilson and Maconachie, 2009; Smith et al, 2012). The results are remarkably consistent: EITI has not only failed to deliver on its stated goals of better natural resource management and a reduction in corruption and conflict but in many cases has led to further marginalization of communities negatively impacted by mining.…”
Section: Power and Legitimacy In Corporate Social Responsibility Govementioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, available evidence on corporate disclosure indicates otherwise – as Brown et al (2009: 572) found in their analysis of the Global Reporting Initiative Sustainability Reporting Guidelines, corporate information disclosure had ‘little impact in shifting the balance of power in corporate governance toward civil society’. Since its launch in 2002, there have been extensive studies about the effectiveness of EITI particularly in the conflict regions of Africa (Andrews, 2016; Haufler, 2010; Hilson and Maconachie, 2009; Smith et al, 2012). The results are remarkably consistent: EITI has not only failed to deliver on its stated goals of better natural resource management and a reduction in corruption and conflict but in many cases has led to further marginalization of communities negatively impacted by mining.…”
Section: Power and Legitimacy In Corporate Social Responsibility Govementioning
confidence: 99%
“…The results are remarkably consistent: EITI has not only failed to deliver on its stated goals of better natural resource management and a reduction in corruption and conflict but in many cases has led to further marginalization of communities negatively impacted by mining. The voluntary nature of disclosure, variability in the accuracy of the data provided, differing stakeholder expectations, asymmetrical power relations, institutional disinterest in policy reform and disparities between mining royalties and positive developmental outcomes were the main factors that made EITI ineffective in natural resource governance (Andrews, 2016). EITI served as a legitimating device for countries and corporations to commit to reform but did not result in delivering reforms or reducing corruption.…”
Section: Power and Legitimacy In Corporate Social Responsibility Govementioning
confidence: 99%
“…As such, Caspary (2012) agrees that the demand for transparency via initiatives like EITI needs to be complemented with other political and economic reforms that empower citizens to hold their government accountable. Andrews (2016) similarly observes that it is problematic to ascribe to one initiative the answer to all the challenges associated with the extractive sector.…”
Section: Theore Ti C Al Liter Ature On Eiti and G Heitimentioning
confidence: 99%
“…That is why the cap on the scope of publicly accessible information in the petroleum sector through the RTI law jeopardises open governance. This is compounded by what Andrews (2016) refers to as the Ghanaian government's failure to allow the full participation of CSOs (important stakeholders) in Ghana's EITI. In addition, the embeddedness of Ghana's EITI in the Ministry of Finance has been criticised as it reduces its ability to be autonomous and increases its susceptibility to government's political manipulation (Andrews 2016;Nguyen-Thanh & Schnell 2009;Oppong & Andrews 2020).…”
Section: Public Interest Accountability Mechanisms and The Annual Bud...mentioning
confidence: 99%